Variability in Reaction of Ife Brown (Irawo) to the Cowpea Aphidborne Mosaic Virus - FATUNLA , TUNDE; LADIPO, J.L. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Cowpea (Vigna unguiculata s.sp. unguiculata) (L.) Walp. cv. Ife Brown showed genetic variability for resistance to cowpea aphid-borne mosaic virus. was shown that Alabunch and Westbred, two Ife Brown parents, carry resistance genes to the virus in their populations. Two generations of individual plant selection in Ife Brown resulted in the production of four true breeding lines resistant to the cowpea aphid-borne mosaic virus.